KARAKTERISTIK BERPIKIR KREATIF DALAM PEMECAHAN MASALAH MATEMATIKA BERDASARKAN GENDER - Zamzam, Kenys Fadhilah; Ambarawati, Mika (Universitas Insan Budi Utomo, 2023)
The purpose of this study was to describe the differences in the characteristics of the ability to think creatively between women and men in solving mathematical problems through an open description test. The research subjects were students of IKIP Budi Utomo Malang semester 3 Mathematics Education Study Program. The mathematical problem solving provided is mathematical problems that require divergent thinking in solving them. This research is a qualitative-descriptive research in which to determine the characteristics of the ability to think creatively through a mathematical problem solving test. The purpose of this research is to describe the different characteristics between women and men in solving math problems. Based on the results of the analysis, it is said that a person has different creative potential both from the characteristics of creative thinking and the creative point of view he has. A person's ability to think creatively is due to the person's personal characteristics, problem characteristics, and point of view. A person is able to develop the creative potential contained in him by getting to know more about the characteristics of the ability to think creatively, especially what aspects stand out.